'A singer is a group': creating a 'researcher template' to uncover complexities in the participatory arts project rocsa singers. Issue 3 (3rd May 2016) - Deceur, Evelyne; Roets, Griet; Rutten, Kris; Bouverne-De Bie, Maria
Abstract: In this article, we seek to merge an insider with an outsider perspective on participatory arts projects, by engaging with the ethnographic turn in arts and promoting the idea of a 'researcher template' (Goodley 1999) as a way of enabling reflexivity in practice-led inquiries. Situated at the intersection between artistic, educational and academic work, this template allows us to address and reflect upon the complexities and vicissitudes emerging from an interpretative study of the Ghent-based participatory arts project, rocsa singers . While revealing the roles of the diverse protagonists within this practice, we highlight three main challenges and tensions: (1) nurturing and supporting diversity; (2) the thin line between directing and going along; and (3) the need to go public. We argue that participatory arts practices form a tempting field to move beyond dominant interpretations and well-known (art) strategies and forms. 'Having one foot in and one foot out' invites us to become aware of this potential, to grasp the continuous and subtle interplay between contextualisation, diversity and responsibility, and to forge new connections between life-worlds and system pressures and priorities.